Optimization of Dikmas Lantas Unit Kamsel Satlantas in Reducing Traffic Accidents to Realize Kamseltibcar at Polres Jepara (Indonesian Journal of Police Studies, 2024)
Indonesia is a developing country, where there is an increasing population. In connction with this, it cannot be separated from the increase in the number of vehicles used by the community. At this time, the vehicle is a primary need for society. According to the Central Bureau of Statistics in 2020, the number of motorized vehicles has increase by 5,6 percent annually. With this increase, it cannor be separated from the increase in the number of traffic jams, violations, and accidents. ne of the factors of traffic accidents is the human factor. There are still many Indonesian people who do not understand the procedures for driving a vehicle that is good and right. This is a problem that must be faced by the Kamsel Satlantas Unit as a preemptive function in reducing the number of traffic accidents. The purpose of this research is to describe the methods and ways of optimizing the activities of dikmas lantas Unit Kamsel Satlantas Polres Jepara in reducing traffic accidents in order to realize the direct security check-in. The author uses qualitative methods to obtain data. The theory used in this study is management theory, SWOT theory, and organizational resource theory, and uses the concept of dikmas then. This research was conducted at the Jepara Traffic Police Unit which obtained data that traffic accidents were still rampant in Jepara Regency. This increase is due to the people in Jepara Regency still not understanding about good and correct driving procedures. It is the responsibility of the Jepara Police Traffic Unit to reduce the number of accidents and traffic violations.
Keywords: Kecelakaan Lalu Lintas; Dikmas Lantas